2022
DOI: 10.1111/beer.12447
|View full text |Cite
|
Sign up to set email alerts
|

Ethical consumerism and wage levels: Evidence from an experimental market

Abstract: This paper contributes to the promotion of multidisciplinary research on ethical consumerism by providing experimental evidence on consumer's willingness to reward sellers by paying higher wages to their workers. We analyze repeated interactions occurring between workers, sellers, and consumers within the framework of an experimental market. By successfully performing a task, workers allow sellers to offer a good through a market. Sellers set the price of goods and decide the wages of workers. Consumers enter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…On the one hand, increased consumer pressure indicates that consumers are willing to pay for environmentally friendly products (Wong, 2013); hence the company will devote more resources to innovating new eco‐friendly products (Zhang & Zhu, 2019). This contrasts with Degli Antoni and Faillo (2022) who suggested that consumers, from an ethical perspective, may be less willing to reward the firm by paying their workers higher wages, believing that such sacrifice should be fully borne by their firm. Furthermore, by responding quickly to consumer pressure, businesses can form beneficial and diversified networks with their customers and get fresh and innovative ideas to aid in innovating eco‐friendly products (Roome & Wijen, 2006).…”
Section: Theoretical Backgroundmentioning
confidence: 79%
“…On the one hand, increased consumer pressure indicates that consumers are willing to pay for environmentally friendly products (Wong, 2013); hence the company will devote more resources to innovating new eco‐friendly products (Zhang & Zhu, 2019). This contrasts with Degli Antoni and Faillo (2022) who suggested that consumers, from an ethical perspective, may be less willing to reward the firm by paying their workers higher wages, believing that such sacrifice should be fully borne by their firm. Furthermore, by responding quickly to consumer pressure, businesses can form beneficial and diversified networks with their customers and get fresh and innovative ideas to aid in innovating eco‐friendly products (Roome & Wijen, 2006).…”
Section: Theoretical Backgroundmentioning
confidence: 79%
“…O consumerismo de base ética envolve uma decisão consciente em consumir produtos de forma seletiva, com base nas crenças e valores morais do individuo sendo uma manifestação de preocupação moral com os produtos e organizações (Cho & Krasser, 2011;Dholakia et al, 2018;Lee, 2021;Antoni & Faillo, 2022). Teorização seminal de Smith (1990) sobre o consumerismo ético considerava o mesmo numa perspetiva negativa ao associar o consumerismo com a oposição por parte dos consumidores a certos produtos, marcas ou organizações.…”
Section: Consumerismounclassified